Conserved Structural Mechanisms for Autoinhibition in IpaH Ubiquitin Ligases - Chou, Yang-Chieh (American Society for Biochemistry and Molecular Biology, 2012)
The IpaH family of novel E3 ligase (NEL) enzymes occur in a variety of pathogenic and commensal bacteria that interact with eukaryotic hosts. We demonstrate that the leucine-rich repeat (LRR) substrate recognition domains of different IpaH enzymes autoinhibit the enzymatic activity of the adjacent catalytic novel E3 ligase domain by two distinct but conserved structural mechanisms. Autoinhibition is required for the in vivo biological activity of two IpaH enzymes in a eukaryotic model system. Autoinhibition was retro-engineered into a constitutively active IpaH enzyme from Yersinia pestis by introduction of single site substitutions, thereby demonstrating the conservation of autoregulatory infrastructure across the IpaH enzyme family.